Present status and future prospects of Gir cow - GAJBHIYE, P U; GADARIYA, M R; AHLAWAT, A R; DONGRE, V B (The Indian Journal of Animal Sciences, 2016)
Gir cattle in Saurashtra provide milk, manure and draught power. Animal genetic resources of native breeds are largely underutilized in India and indiscriminate crossbreeding has degraded large numbers of local breeds. This is also true with Gir cattle in its native breeding tract. (i) About two-third population is either graded Gir or Gir like and hence not pure Gir, (ii) only one-third population i.e. 7.6 lakh could be 95% towards pure Gir. Hence, it is difficult to obtain large number of pure Gir animals. Since 2003–04 to 2012– 13, contribution of Saurashtra to state total indigenous cattle milk yield is 60%. A 25 years data analysis on Gir cows at CBF revealed average lactation yield as 2029 litre in 321 days lactation length and 1843.8 litre milk yield in 300 days. Production performance of Gir cows in three districts:(1) Junagadh (2) Rajkot and (3) Bhavnagar showed that average test day milk yield in Gir cows over a lactation were 7.99±0.05 litre/d for Junagadh, 6.43±0.03 litre/d for Rajkot and 6.71±0.04 litre /d for Bhavnagar district, projected values for 300-days milk yield being was 2397, 1929, and 2013 litre for the three districts respectively. Average AFC in Gir cattle of the station herd was 1527.7±14.1 days (51 mth) whereas survey study in Junagadh, Rajkot and Bhavnagar districts indicated AFC in field Gir cows as 45, 49, and 46 month, respectively. Parity had a significant effect on total lactation milk yield in Gir cows at CBF. Highest total lactation yield was observed in 2nd lactation (2132±123.4 litre) while lowest was observed in 10th lactation (1456.8±219.1 litre). Milk production traits LY and 300-d LY exhibited 10 to 13 % genetic variability in the herd. This suggests that to increase variability in the herd, genetic material from outside herd needs to be introduced.